Efeito de sistemas de cultivo e de fungicidas na severidade de doenças fúngicas em pepino partenocárpico (cucumis sativus l.) em ambiente protegido - Maraus, Paulo Francisco (2013)
The Japanese cucumber is one of the most grown vegetables in protected environments, which provides control of some environmental factors, improving yield, quality and reducing the seasonality. However, many problems might arise due to improper use of the structures, favoring disease severity regarding outdoors. Some diseases might be favored by conditions inside the greenhouse, like cucurbit downy mildew (Pseudoperonospora cubensis) and powdery mildew (Oidium spp.) whose development is strongly linked to environmental conditions, and also the gummy stem blight (Didymella bryoniae) which is also influenced by the soil inoculum, crop residues and the transmission by infected seeds. Therefore, the adjustment of internal greenhouse environment in order to discourage the pathogens and promote the crops is essential to ensure the success of protected cultivation. Thereby, sought to verify the effect of cropping systems and fungicide spraying on disease development and changes in qualitative patterns of protected cucumber crop in subtropical climate. The treatments consisted of: 1) hydroponics without fungicide (HF-), 2) hydroponics with fungicide (HF+), 3) soil without fungicide (SF-), 4) soil with fungicide (SF+), 5) "mulching" without fungicide (MF-) and 6) "mulching" with fungicide (MF+). The variables evaluated throughout the crop cycle were: severity of the disease, the area under the disease progress curve (AUDPC), plant height, number and quality of fruits. Hydroponics yield was slightly lower, but with higher proportion of straight fruits with more market value. Fungicide spraying isolated was effective only to control powdery mildew, showing low efficiency over the downy mildew and gummy stem blight. The fungicide spraying within hydroponics system secured a more expressive disease control. In general, the disease development was more limiting to cucumber crop during the winter, with severity ranging from two to five times higher than in the summer. The downy mildew has shown to be the most limiting disease to cucumber, mainly during the winter. Regarding the cropping systems studied, hydroponics presented the lowest incidence of gummy stem blight and downy mildew, and higher severity of powdery mildew than the other systems.